Virtually organic beef - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
From September 2 to October 15, 2002, join in an online conference on organic beef production. Each week will have a different focus: Agroecology and sustainable production; welfare and animal health; food and nutrition; meat quality; economic and...